2003
DOI: 10.4028/www.scientific.net/msf.414-415.281
|View full text |Cite
|
Sign up to set email alerts
|

Deforming Texture Effect on Phase Transformation in Stainless Steels

Abstract: In stainless steels during the non-equilibrium transformation of austenite the deformed bcc a' martensite and hexagonal, non-magnetic e martensite also can form. These transformations can be induced by cooling (under critical temperature) and/or mechanical deformation. The appearance of e martensite has an effect on the deformation ability and other properties. The experimental results associate the e martensite formation with the plastic deformation behaviour (TRIP effect), while the transformation of e marte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…To describe the texture view of deformed samples a special inverse pole figure was used based on the X-ray diffraction data. This method-described in detail in an earlier paper [7]-is very useful for quantitative comparison of changing during deformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To describe the texture view of deformed samples a special inverse pole figure was used based on the X-ray diffraction data. This method-described in detail in an earlier paper [7]-is very useful for quantitative comparison of changing during deformation.…”
Section: Methodsmentioning
confidence: 99%
“…In these materials there is always a texture [6] due to the deformation that continuously changes owing to the thermomechanical treatments and the anisotrope transformation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since planar slip is integral to the transformation, the propensity for strain-induced martensite is not only a function of austenite stability but depends also on stacking fault energy (SFE), as proposed by Olson and Cohen. [1] Although it appears that the transformation may progress initially by the formation of a transitional epsilon phase, it has been shown [8,9,10] that as strain progresses, the transformation to epsilon stops and existing epsilon is completely consumed at relatively low levels of strain and that austenite transforms directly to martensite at higher levels of strain. Brooks et al [11,12] showed that martensite formed directly from dislocation pileups on {111} ␥ slip planes in low carbon austenitic stainless steels, including 304L, without a transitional phase.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, these steels have become a potential alternative for crash relevant steels for the automotive industry due to a very pronounced TRIP effect. Some of the austenitic stainless steels are metastable at room temperature and undergo martensitic transformation on being plastically deformed . The formation of martensite increases the work hardening rate resulting in high ultimate tensile strength and good uniform elongation .…”
Section: Introductionmentioning
confidence: 99%